Techno-economic Influence on Malaysia’s Solar Thermal Installation for Heating Process - Anis Sabirin Baharom; Nofri Yenita Dahlan (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents System Dynamics simulation and Techno-Economic analysis to estimate the techno-economic benefits and reliabilities of solar heating. The study focuses only on industrial heat process in Malaysia. The main objective of the current work was to investigate the solar thermal installation feasibility by Malaysian industrial heat process for next 20 years. The solar thermal installation was measured through the techno-economic feasibility (TEF) study by developing the TEF model using System Dynamics Simulation (SDS). subsidy, net solar thermal cost, and NPV are used as economic influence factors. System performance, solar thermal life time, energy, solar fraction and size of collector area are used as technical influence parameters. Results have shown that the economic factor has a bigger influence on solar thermal installation capacity in Malaysia. The technical factors only contribute small percentage to the installation percentage. Policy maker could benefit from the outcomes obtained as a guideline.